Hemophilia presenting as recurrent ocular hemorrhage - Aquino, Luis Miguel (GMS Ophthalmology Cases, 2020)
Objective: Patients with hereditary bleeding disorders rarely present with intraocular or orbital hemorrhage as the initial symptom. The presence of such a condition can be easily overlooked when contemplating ophthalmic surgery, and can give rise to intraoperative and postoperative complications. Awareness of such conditions can improve surgical decisions.Methods: This is a case report of an eight-year-old Filipino male who sustained blunt trauma to his right eye, causing traumatic total hyphema with corneal staining. Subretinal hemorrhage was seen on ultrasound. The patient underwent anterior chamber washout with temporary keratoprosthesis and pars plana vitrectomy with silicone oil tamponade. Clearance of the hyphema was noted postoperatively. However, on follow-up after 19 days, the patient presented with recurrence of hyphema, new onset proptosis and peribulbar hemorrhage.Results: Imaging of the orbit revealed new-onset pseudoproptosis with intraocular and peribulbar hemorrhage. A bleeding disorder was suspected at this point. Further probing revealed a family history of prolonged bleeding time in an X-linked genetic inheritance pattern spanning three generations. Laboratory testing of prothrombin, partial thromboplastin, and factor assays were done, which revealed factor VIII deficiency, diagnostic of hemophilia A. No further surgery was done. The patient was given transfusions of fresh frozen plasma, which resolved the hemorrhage.Conclusions: Bleeding disorders present a dilemma in the surgical management of patients. In cases of traumatic hemorrhage, adequate history and physical examination should always be done to rule these out. Surgical outcomes in hemophiliacs can be improved with preoperative prophylactic treatment and close postoperative monitoring and care.